Investigation and Demonstration of High Speed Full-Optical Hybrid FSO/Fiber Communication System Under Light Sand Storm Condition - Maged Abdullah Esmail; Amr Ragheb; Habib Fathallah; Mohamed-Slim Alouini (IEEE Photonics Journal)
In contrast to traditional free space optical (FSO) systems, the new generation is aimed to be transparent to optical fiber where protocols, high signal bandwidths, and high data rates over fiber are all maintained. In this paper, we experimentally demonstrate a high speed outdoor full-optical FSO communication system over 100 m link. We first describe the design of our transmitter, which consists of a comb generator and a flexible multiformat transmitter. Our measurements are performed in arid desert area under a light dust storm. In this environment, we use a 12 subcarrier comb generator, each of which is modulated by a quadrature-amplitude modulation (QAM) signal. We achieved a 1.08 Tbps error free data rate with 3.6 b/s/Hz spectral efficiency. We place long optical fiber rolls in the transmitter side and the receiver side to mimic real FSO deployments. Furthermore, we investigated the effect of receiver misalignment in outdoor conditions and the effect of background noise. We find that full-optical FSO system is sensitive to the misalignment effect. However, the background noise has negligible effect. Finally, we find that solar heating of the transceiver causes collimator deviation, which requires using a cooling unit or auto tracking system.